2016
DOI: 10.1007/s00540-016-2213-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aspirin use on morbidity and mortality in massively transfused cardiac surgery patients: a propensity score matched cohort study

Abstract: Preoperative aspirin use is not associated with decreased in-hospital mortality in massively transfused cardiac surgery patients, but may be associated with less mechanical lung ventilation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…The minimum number of RBCs in MRT has been variously set at 4, [3] 5, [17] 6, [9] or 8, [28] and we opted for 4 as our cut-off because morbidity sharply increases beyond this level, [8] and postoperative complications even increase 19.4% ( P < .01) when the patients receive ≥4 units of RBCs. [29]…”
Section: Discussionmentioning
confidence: 99%
“…The minimum number of RBCs in MRT has been variously set at 4, [3] 5, [17] 6, [9] or 8, [28] and we opted for 4 as our cut-off because morbidity sharply increases beyond this level, [8] and postoperative complications even increase 19.4% ( P < .01) when the patients receive ≥4 units of RBCs. [29]…”
Section: Discussionmentioning
confidence: 99%
“…Search results: From 858 initial citations, six eligible studies, which included a total of 11,406 patients, were identified in the present meta-analysis [Hur 2017;Mazzeffi 2016;Huang 2015;Yao 2015;Myles 2016], with 6,280 patients in the aspirin group and 5,126 in the control group. Characteristics of the included studies and patients are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the above concerns, some studies also found protective effect of preoperative aspirin on CSA-AKI [Hur 2017;Huang 2015;Yao 2015;. Other studies found no positive effect of preoperative aspirin [Mazzeffi 2016;Myles 2016].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, perioperative aspirin use may be beneficial in cardiac surgery, decreasing complications such as MI and renal failure after surgery [121315]. Aspirin may even confer a lung protective effect after massive transfusion after cardiac surgery as reported in one observational study [16]. …”
Section: Platelet Inhibitors and Cardiac Surgerymentioning
confidence: 99%